Research and bioethic - Quezada Zevallos, Jenny (2023)
We are at the moment in which human being may be informed of the objectives, risk and period of time of their participation in research, asking them for their written consent. In this article bioethics is explained briefly ant the international ethical rules document for biomedical research with human being (1996) is also summarized. We consider the necessary revealing among researchers and the fulfilment of its use in research with human being.